Pupil tracking optical coherence tomography for precise control of pupil entry position - Carrasco-Zevallos, Oscar (Biomed Opt Express, 2015)
To maximize the collection efficiency of back-scattered light, and to minimize aberrations and vignetting, the lateral position of the scan pivot of an optical coherence tomography (OCT) retinal scanner should be imaged to the center of the ocular pupil. Additionally, several retinal structures including Henle’s Fiber Layer (HFL) exhibit reflectivities that depend on illumination angle, which can be controlled by varying the pupil entry position of the OCT beam. In this work, we describe an automated method for controlling the lateral pupil entry position in retinal OCT by utilizing pupil tracking in conjunction with a 2D fast steering mirror placed conjugate to the retinal plane. We demonstrate that pupil tracking prevents lateral motion artifacts from impeding desired pupil entry locations, and enables precise pupil entry positioning and therefore control of the illumination angle of incidence at the retinal plane. We use our prototype pupil tracking OCT system to directly visualize the obliquely oriented HFL.